Menggali Makna Tafakkur Dalam QS. Al-A’raf Ayat 176 - Rahmania, Puput; Surahman, Cucu; Sumarna, Elan; Batula, Abu Warasy (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to analyze the meaning of tafakkur (deep reflection) in Surah Al-A'raf verse 176 and examine its relevance to spiritual, moral, and social education in contemporary Islam. This research employed a qualitative approach with library research methodology, involving the analysis of classical tafsir literature such as Tafsir Ibn Kathir, Tafsir al-Qurtubi, and Tafsir al-Razi, as well as contemporary interpretations by Sayyid Qutb and M. Quraish Shihab. The tahlili (analytical) and descriptive methods were used to interpret the meaning of tafakkur, while content analysis was applied to identify educational values embedded within the verse. The results indicate that tafakkur in QS. Al-A'raf 176 encompasses three interconnected dimensions: (1) spiritual dimension, which cultivates awareness and closeness to Allah; (2) moral dimension, which functions as a mechanism for self-control and ethical guidance; and (3) social dimension, which encourages individuals to apply reflective wisdom in constructive social interactions. These values can be integrated into contemporary Islamic education through pedagogical methods that emphasize reflection, discussion, case studies, and social practice. This study contributes to the development of holistic Islamic education that produces students who are not only intellectually competent but also spiritually mature, morally upright, and socially responsible. The findings underscore the critical importance of tafakkur as a foundation for character development in facing the challenges of modern education.